Using near-infrared reflectance spectroscopy for rapid nutrient evaluation of sorghum silage - Budiongo, K.J.; Harbers, L.H.; Seabourn, B.W.; Bolsen, K.K.; Brent, B.E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This research was designed to develop a set of prediction equations to measure nutrient composition of Kansas sorghum silages by near-infrared reflectance spectroscopy (NIRS). Because sorghum silages are highly variable in grain content, we included a large number of cultivars to develop a robust set of equations for dry matter, crude protein, neutral detergent fiber, and acid detergent fiber. The results indicate that NIRS analysis of sorghum silages is feasible.
Keywords: Beef; Sorghum silage; Nutrient evaluation; Near-infrared reflectance spectroscopy